Design and Testing of a Pid Controller on a Parrot Minidrone - Hrishitva patel (Eduvest - Journal of Universal Studies, 2022)
This paper focuses on quadcopter control design and uses the Simulink Support Package for Parrot Minidrones to test various control approaches. This project's goal is to bridge the knowledge gap between control design and implementation, making it simpler to comprehend the fundamental ideas of control theory. Obtaining a dynamic model of the quadcopter, linearizing the system around an equilibrium point, designing PID controller on the linearized system, and then verifying the controllers on the non-linear model using simulations and test flights with the actual drone are the key components of this research. The tuned controllers are validated by trajectory tracking, setpoint regulation, and disturbance rejection.